Epidemiological Characteristics and Transmission Patterns of COVID-19 Cases Among Children and Adolescents Aged 0–18 Years in South Korea - Jang J; Hwang MJ; Kim YY; Park SY; Yoo M; Kim SS; Lee S; Kwon D (Dove Medical Press, 2022)
Jinhwa Jang,1 Myung-Jae Hwang,1 Yoo-Yeon Kim,1 Shin Young Park,1 Myeongsu Yoo,1 Seong-Sun Kim,1 Sangwon Lee,2 Donghyok Kwon1 1Division of Public Health Emergency Response Research, Korea Disease Control and Prevention Agency, Cheongju-si, Chungcheongbuk-do, Republic of Korea; 2Director General for Public Health Emergency Preparedness, Korea Disease Control and Prevention Agency, Cheongju-si, Chungcheongbuk-do, Republic of KoreaCorrespondence: Donghyok Kwon, Division of Public Health Emergency Response Research, Korea Disease Control and Prevention Agency, 187, OsongSaengmyeong 2-ro, Osong-eup, Heungdeok-gu, Cheongju-si, Chungcheongbuk-do, 28159, Republic of Korea, Tel +82-43-719-7730, Fax +82-43-719-7749, Email vethyok@korea.krBackground: In South Korea, the epidemiological characteristics of children and adolescents infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) have not been reported to date. The purpose of this study was to identify major epidemiological characteristics and transmission patterns of coronavirus disease 2019 (COVID-19) in children and adolescents.Methods: This study was conducted through a system integrated in an epidemiological investigation by the Korea Disease Control and Prevention Agency from January 20, 2020, to June 5, 2021. We analyzed the epidemiological characteristics of 14,967 children and adolescents with COVID-19 according to the age groups and transmission age patterns of 3721 infector-infectee pairs in South Korea.Results: Among the total confirmed COVID-19 cases, 14,967 patients were aged 0- 18 years. The most affected age group among children and adolescents were those aged 16- 18 years (3589, 24.0%). For all age groups, the infection route through friends and family members (31.9%) was the highest. For the contact age pattern analysis, infection from infectors aged 30- 49 years to infectees aged 0- 12 years showed a statistically significant relation (p < 0.001) compared to that in other age groups. On the other hand, among the infectees aged 13- 15 years and 16- 18 years were significantly related with adolescents aged 10- 19 years (p < 0.05).Conclusion: These results suggest that adolescents aged 13- 18 years were more infected with COVID-19 than those aged 0- 12 years. Furthermore, they are particularly more likely to be infected by friends and family members. Besides, in patients aged 13- 18 years, transmission of SARS-CoV-2 was more common from adolescents to adolescents than from adults to adolescents. This research will provide scientific evidence for school policies and vaccine strategies for COVID-19 prevention in children and adolescents.Keywords: coronavirus disease-2019, severe acute respiratory syndrome coronavirus-2, incidence rate, mortality